Estudo do mecanismo eletroforético de coleta na filtração de aerossóis - Mello, Rafael Lopes Seabra de (2007)
Previous works have shown that the presence of electrostatic forces in particles significantly affect the performance of a filter, both increasing collection efficiency and reducing pressure drop. Recently, in the Environmental Control research group of the Chemical Engineering Department of UFSCar, Rodrigues (2005) have studied the filtration of electric charged phosphate rock particles in polypropylene filter, observing the influence of the charge acquired by the particles in collection efficiency and pressure drop. The aim of the present work is to analyze the particle trajectory during filtration and the contribution level of each collect mechanism present in the process, in order to theoretically detail the results obtained by Rodrigues (2005) and propose a model for the electrophoretic mechanism of collection that better fit in experimental data.